Relative age effect in team and individual sports: A systematic review with quantitative synthesis - Agricola, A. (European Journal of Human Movement, 2026)
The Relative Age Effect (RAE) influences talent identification and athlete development across sports. This study presents a systematic review with a secondary quantitative synthesis of extracted or calculated odds ratios (ORs) to examine the magnitude and variability of RAE in selected team sports (football, ice hockey, basketball) and individual sports (tennis, swimming, gymnastics). A total of 91 peer-reviewed studies comprising 158 samples and more than 40,000 athletes aged 8-18 years were included. ORs were defined as the likelihood of being relatively older versus relatively younger within an age cohort and were extracted when reported or calculated from birthdate frequency distributions using comparisons between the earliest and latest birth quartiles. Team sports showed a consistent, moderate RAE (mean ORs approximately 1.28-1.32), whereas individual sports demonstrated greater variability, with gymnastics showing the strongest effect (mean OR = 2.10) and swimming the weakest (mean OR = 1.20). Exploratory comparisons suggested differences in the distribution of ORs between team and individual sports. Overall, these findings indicate that RAE is not uniform across sport contexts but is shaped by sport-specific demands and selection practices. Practical strategies such as bio-banding, flexible competition formats, and increased awareness among coaches and administrators may help mitigate selection bias and support more equitable developmental pathways.